MOLECULAR BEAM EPITAXY (Лучшие интеллектуальные исследования, 2025)
Abstract. Molecular Beam Epitaxy (MBE) is a highly precise thin-film deposition technique used for the growth of single-crystal semiconductor layers under ultra-high vacuum conditions. By enabling atomic-scale control over composition and thickness, MBE has become an indispensable tool in the fabrication of advanced electronic and optoelectronic devices, including high-speed transistors, quantum wells, quantum dots, superlattices, and laser diodes.